Interrogating heterogeneous compaction of analogue materials at the mesoscale through numerical modeling and experiments - Derrick, J; Rutherford, M; Davison, T; Chapman, D; Eakins, D; Collins, G (AIP Publishing, 2018)
Meteorites are classified by their relative exposure to three processes: aqueous alteration; thermal metamorphism; and shock processes. They constitute the main evidence available for the conditions in the early solar system. The precursor material to meteorites was bimodal and consisted of large spherical melt droplets (chondrules) surrounded by an extremely fine porous dust (matrix) with a high bulk porosity (> 50%). We present experiments and simulations, developed in tandem, investigating the heterogeneous compaction of matter analogous to these precursor materials. Experiments were performed at the European Synchrotron Radiation Facility (ESRF) where radiographs of the shock compaction and wave propagation were taken in-situ and in real time. Mesoscale simulations were performed using a shock physics code to investigate the heterogeneous response of these mixtures to shock loading. Two simple scenarios were considered in which the compacted material was pure matrix or pure matrix with a single inclusion. Good agreement was found between experiment and model in terms of shock position and relative compaction in the matrix. In addition, spatial variation in post-shock compaction was observed around the single inclusion despite uniform pre-shock porosity in the matrix. This shock-induced anisotropy in compaction could provide a new way of decoding the magnitude and direction by which a meteorite was shocked in the past.